Innovative and Investment Development of the Russian Federation: Regional Aspect - Anastasia Kurilova; Anna Kiryushkina; Sofia Savenkova (Communications of International Proceedings, 2020)
Innovative and investment development of territories is an important element in the development of the country's economy. The article examines the factors that influence the investment and innovative development of the regions of the Russian Federation. The degree of influence of factors is determined through the construction of an econometric model. Modeling is carried out through the Gretl 1.9.11 software product using the least squares method.
Keywords: Innovative Development of Territories; Investment Development of Territories; Regional Economic Development.